Implementasi Metode Weighted Moving Average Untuk Sistem Peramalan Penjualan Markas Coffee - Muchamad Rizqi; Antonius Cahya; Nova El Maida (Faculty of Computer Science, University of Jember, 2021)
Headquarters Coffee is one of the businesses engaged in the culinary field of coffee drinks. The problem that occurs at the Coffee Headquarters is that business activities are still carried out manually. In addition, determining sales in the next period only refers to the sales data of the previous period, resulting in owners often experiencing shortages or excess stocks of coffee to be sold due to uncertain sales. Therefore we need a forecasting method (Forecasting) that is appropriate and can be applied to an Information System in the form of a Website. The purpose of making this forecasting information system is to assist companies in recording sales to make it more practical by applying the Weighted Moving Average (WMA) method. From the results of the calculation of the WMA method, the level of accuracy will then be calculated using the Mean Absolute Percentage Error (MAPE) method. The results of forecasting by applying the WMA method and MAPE calculations on weights 3, 4 and 5 show that the Robusta coffee on the Robusta menu which has the smallest MAPE is weight 3 with a calculation result of 19.2499 and the Robusta Milk menu which has the smallest MAPE is weight 4 with the calculation result is 15.21879166 and Excelsa coffee on the excelsa menu which has the smallest MAPE is weight 3 with a calculation result of 19.1538 and the Excelsa Susu menu which has the smallest MAPE is weight 5 with a calculation of 17.27650182 while for Arabica coffee on the Arabica menu which has the smallest MAPE is weight 4 with a calculation result of 18.1735 and the Arabica Susu menu which has the smallest MAPE is weight 5 with a calculation result of 16.24012072. Where the Mape value produced by each type of coffee is still below 20%, which means the forecasting results can be categorized as good.